Persistence with Early-Line Abatacept versus Tumor Necrosis Factor-Inhibitors for Rheumatoid Arthritis Complicated by Poor Prognostic Factors - Xue Han; Francis Lobo; Michael S. Broder; Eunice Chang; Sarah N. Gibbs; David J. Ridley; Irina Yermilov (Journal of Health Economics and Outcomes Research)
**Background:** Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by joint swelling and destruction that leads to severe disability. There are no clear guidelines regarding the order of therapies. Gathering data on treatment patterns outside of a clinical trial setting can provide useful context for clinicians.